The influence of POLST on treatment intensity at the end of life: A systematic review. Issue 12 (22nd September 2021) - Vranas, Kelly C.; Plinke, Wesley; Bourne, Donald; Kansagara, Devan; Lee, Robert Y.; Kross, Erin K.; Slatore, Christopher G.; Sullivan, Donald R.
Abstract: Background: Despite its widespread implementation, it is unclear whether Physician Orders for Life‐Sustaining Treatment (POLST) are safe and improve the delivery of care that patients desire. We sought to systematically review the influence of POLST on treatment intensity among patients with serious illness and/or frailty. Methods: We performed a systematic review of POLST and similar programs using MEDLINE, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, Cochrane Database for Systematic Reviews, and PsycINFO, from inception through February 28, 2020. We included adults with serious illness and/or frailty with life expectancy <1 year. Primary outcomes included place of death and receipt of high‐intensity treatment (i.e., hospitalization in the last 30‐ and 90‐days of life, ICU admission in the last 30‐days of life, and number of care setting transitions in last week of life). Results: Among 104, 554 patients across 20 observational studies, 27, 090 had POLST. No randomized controlled trials were identified. The mean age of POLST users was 78.7 years, 55.3% were female, and 93.0% were white. The majority of POLST users (55.3%) had orders for comfort measures only. Most studies showed that, compared to full treatment orders on POLST, treatment limitations were associated with decreased in‐hospital death and receipt of high‐intensity treatment, particularly in pre‐hospital settings. However, in the acute care setting, a sizable number of patients likely received POLST‐discordant care. The overall strength of evidence was moderate based on eight retrospective cohort studies of good quality that showed a consistent, similar direction of outcomes with moderate‐to‐large effect sizes. Conclusion: We found moderate strength of evidence that treatment limitations on POLST may reduce treatment intensity among patients with serious illness. However, the evidence base is limited and demonstrates potential unintended consequences of POLST. We identify several important knowledge gaps that should be addressed to help maximize benefits and minimize risks of POLST.